2016
DOI: 10.1007/s13730-016-0244-z
|View full text |Cite
|
Sign up to set email alerts
|

A case of rapid amelioration of hepatitis C virus-associated cryoglobulinemic membranoproliferative glomerulonephritis treated by interferon-free directly acting antivirals for HCV in the absence of immunosuppressant

Abstract: Mixed cryoglobulinemic syndrome, which is a systemic vasculitis characterized by the immune complex deposition in small-and medium-sized arteries and most often due to chronic hepatitis C virus (HCV) infection, sometimes clinically manifests as refractory glomerulonephritis or nephritic syndrome. Patients with mixed cryoglobulinemic nephropathy who have a rapidly progressive glomerulonephritis should receive immunosuppressive therapy. After disease stabilization, patients should receive concurrent therapy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
2
6
1
1
Order By: Relevance
“…Overall, the high expression of DNA repair genes that are involved in driving host inflammation could be implicated in long- term cryoglobulinemia relapses. Our data is consistent with work by Obata et al , 2017 showing complete remission of MCV after receiving DAA therapy without immunosuppressant, which was followed by cryoglobulinemia recurrence after 17 months from treatment initiation [ 76 ].…”
Section: Discussionsupporting
confidence: 93%
“…Overall, the high expression of DNA repair genes that are involved in driving host inflammation could be implicated in long- term cryoglobulinemia relapses. Our data is consistent with work by Obata et al , 2017 showing complete remission of MCV after receiving DAA therapy without immunosuppressant, which was followed by cryoglobulinemia recurrence after 17 months from treatment initiation [ 76 ].…”
Section: Discussionsupporting
confidence: 93%
“…HCV-RNA turned out to be negative 6 months later. In contrast to the previous report,4 proteinuria still persisted >1 g/gCr and renal function (Cr, 6.5 mg/dL) further declined at 71 years of age. He developed renal anaemia (Hb, 10.1 g/dL) and was administered epoetin beta pegol monthly 5…”
Section: Case Presentationcontrasting
confidence: 99%
“…Another explanation as to why achievement of SVR12 may not improve renal disease progression is that patients may have intrinsic renal disease prior to treatment, such as MPGN, and these patients will have CKD progression despite achieving SVR12; this has been previously described in the literature in case reports[ 24 ]. However, other reports have suggested that DAA therapy can result in successful treatment of HCV-associated MPGN with improvement in creatinine and proteinuria[ 25 ]. Furthermore, the patient population studied was unique - it is comprised of Veterans who are predominantly male, older in age, have a higher prevalence of CKD compared to the general population, and often have significant co-morbidities associated with CKD, such as diabetes mellitus, hypertension, vascular disease, and cancer[ 26 ].…”
Section: Discussionmentioning
confidence: 99%